Resistance of silicone breast explants under cyclic compressive load as a function of implantation time and explant mass - von Hanstein, Harald; Horch, Raymund E.; Schubert, Dirk W. (Polymer Testing, 2020)
15 micro-textured silicone breast explants are investigated in cyclic compression tests regarding their mechanical behavior. Initially a maximum load of 2.5 kN was applied to the explants in a repetitive way until failure happened. Finally the results are shown on the one hand as a correlation between the number of endured loading cycles and the implantation time. On the other hand the correlation to the explants’ mass was analyzed and described by using a power la
Keywords: Silicone breast explant; cyclic load; implantation time; explant mass; compresssion test; mechanical behavior